2008
DOI: 10.1159/000113732
|View full text |Cite
|
Sign up to set email alerts
|

Steno-Occlusive Arterial Disease and Early Neurological Deterioration in Acute Ischemic Stroke

Abstract: Aim: To evaluate the influence that steno-occlusive arterial disease may have on the development of early neurological deterioration (END) in a large series of patients with acute ischemic stroke. Methods: We studied a prospective cohort of 1,093 patients admitted to a single tertiary hospital with presence of neurological symptoms in the first 24 h after stroke onset. END was defined as any increase in the National Institutes of Health Stroke Scale score ≧4 points in the first 72 h. The arterial study assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 59 publications
4
37
2
Order By: Relevance
“…Similar results have been reported from a study 12 that assessed the arterial status using variable combination of transcranial Doppler, carotid duplex, DSA, MR angiography, and/or CT angiography in 1093 patients (both anterior and posterior circulation strokes). The presence of stenoocclusive disease was significantly associated with END in multiple logistic regression, with occlusion more significantly so than stenosis; the highest adjusted OR was obtained for vertebrobasilar steno-occlusive disease.…”
Section: Hemodynamic Mechanisms Cerebral Perfusion Pressuresupporting
confidence: 86%
See 1 more Smart Citation
“…Similar results have been reported from a study 12 that assessed the arterial status using variable combination of transcranial Doppler, carotid duplex, DSA, MR angiography, and/or CT angiography in 1093 patients (both anterior and posterior circulation strokes). The presence of stenoocclusive disease was significantly associated with END in multiple logistic regression, with occlusion more significantly so than stenosis; the highest adjusted OR was obtained for vertebrobasilar steno-occlusive disease.…”
Section: Hemodynamic Mechanisms Cerebral Perfusion Pressuresupporting
confidence: 86%
“…5,7 The need for an internationally agreed definition has been previously highlighted 10 but not fulfilled so far. However, the National Institutes of Health Stroke Scale has been recently widely used to define END with deterioration Ն4 points during the first 48 3,11 or 72 12 hours being almost consistently used.…”
mentioning
confidence: 99%
“…16 Recent studies have shown a high recurrence risk in the first days after TIA or TIA and minor stroke. 17 However, few data are available concerning recurrence risk in patients with minor stroke, which generally includes early neurological deterioration, 18,19 a factor that may often reflect early recurrence. Moreover, no previous series to our knowledge specifically included patients in the first 6 hours from onset of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…13 Additional data on NIHSS were available for the validation cohort (VC) allowing assessment of early neurological deterioration, defined as an increase of NIHSS score of ≥4 in the first 72 hours after the stroke. 23 Successful reperfusion was assessed by thrombolysis in cerebral infarction scale and defined as thrombolysis in cerebral infarction 2b-3.…”
Section: Outcome Measuresmentioning
confidence: 99%